Analisis Faktor-Faktor Penghambat UMKM Di Indonesia Dalam Melaksanakan Ekspor Selama Pandemi Covid-19 - Fajrul Falaq, M.; Asmara, Kiky (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
The Covid-19 pandemic is an outbreak of spreadingrowth. Exports virus that hit the country around the world.Indonesia is one of the countries in the world affected by the Covid-19 pandemic.With this Covid-19 Pandemic, causing slump in the economy of Indonesian people.MSMEs are one of the sectors affected by the Covid-19 Pandemic.MSMEs are an activity that is carried out by individuals to trade business activities referring to business activities in the field of productive economy.The MSME sector also has a huge export share opportunity in the economy of Indonesia's growth.Exports are an activity of selling foreign goods products by based on a payment system, quantity, quality and requirements in selling other goods products based on approval between the importers and exporters.In this research, the method used is to use a qualitative approach through the narrative analysis method.